Line of demarcation - Woodward, M. P.; Clancy, Tom, 1947-2013 (Clancy, Tom, 1947-2013. Jack Ryan Jr. novel, 2025)
"It starts with the destruction of a US Coast Guard cutter and the loss of her entire crew. But the USCG Claiborne was on an innocuous mission to open a sea lane between an oil field off the coast of Guyana and the refineries of southern Louisiana. The destruction of the ship, tragic as it is, won't stop that mission from continuing. So who would sacrifice twenty-two men and women just to slow down the plan? That's the question plaguing Jack Ryan Jr. He's in Guyana to work a deal to get his company, Hendley Associates, in on the ground floor of this new discovery, but the destruction of the Claiborne and the kidnapping of the Guyanese Interior Minister make it clear that there's a malignant force working to destroy Guyana's oil industry. It's up to Jack to identify the killers before they draw a bead on him, but how can he do that when the line of demarcation between friend and foe is constantly shifting?"--